Supportive supervision from a roving nurse mentor in a community health worker programme: a process evaluation in South Africa - Hlologelo Malatji; Frances Griffiths; Jane Goudge (BMC, 2022)
Abstract Background Many low and middle- income countries (LMICs) are repositioning community health worker (CHW) programmes to provide a more comprehensive range of promotive and preventive services and referrals to the formal health service. However, insufficient supervision, fragmented programmes, and the low literacy levels of CHWs often result in the under-performance of the programmes. We evaluate the impact of a roving nurse mentor working with CHW teams proving supportive supervision in a semi-rural area of South Africa. Methods We conducted a longitudinal process evaluation, using in-depth interviews, focus groups and observations prior to the intervention, during the intervention, and 6 months post-intervention to assess how the effects of the intervention were generated and sustained. Our participants were CHWs, their supervisors, clients and facility staff members and community representatives. Results The nurse mentor operated in an environment of resource shortages, conflicts between CHWs and facility staff, and an active CHW labour union. Over 15 months, the mentor was able to (1) support and train CHWs and their supervisors to gain and practice new skills, (2) address their fears of failing and (3) establish operational systems to address inefficiencies in the CHWs' activities, resulting in improved service provision. Towards the end of the intervention the direct employment of the CHWs by the Department of Health and an increase in their stipend added to their motivation and integration into the local primary care clinic team. However, given the communities' focus on accessing government housing, rather than better healthcare, and volatile nature of the communities, the nurse mentor was not able to establish a collaboration with local structures. Conclusions A roving nurse mentor overseeing several CHW teams within a district healthcare system is a feasible option, particularly in a context where there is a shortage of qualified supervisors to support CHWs activities. A roving nurse mentor can contribute to the knowledge and skills development of the CHWs and enhance the capacity of junior supervisors. However, the long-term sustainability of the effects of intervention is dependent on CHWs' formal employment by the Department of Health.